Health promoting sports federations: theoretical foundations and guidelines - Van Hoye, Aurélie; Geidne, Susanna; Vuillemin, Anne; Dowd, Kieran; Glibo, Iva; Heck, Sandra; Ibsen, Bjarne; Johnson, Stacey; Kingsland, Melanie; Kokko, Sami; Lane, Aoife; Ooms, Linda; et al. (Frontiers in Public Health, 2023)
Background: Researchers and policy-makers have highlighted that the potential for organised sports to promote health has been underexploited. Sports clubs have limited capacity to promote health due to their voluntary nature and have called for support from their national sports federations. The present article provides guidelines, based on the theoretical principles of health promoting sports clubs and an analysis of practical tools and proven strategies, to support national sports federations to invest in health promotion (HP).Methods: A qualitative iterative study was undertaken, based on five two-hour meetings of a group of 15 international researchers in HP in sports clubs. Notes and minutes from meetings, as well as shared outputs were analyzed based on the health promoting sports club framework.Results: Guidelines developed for national sports federations to promote health includes a definition of a health promoting sports federation (HPSF), a description of how the settingsbased approach to HP adapts to national sports federations, as well as practical applications of health promoting sports club's intervention strategies. The analysis of existing tools also demonstrated that most tools are centered on a single dimension of health (social, mental, physical, spiritual or community), and often on a specific health topic. Furthermore, they do not cover HP as a continuous long-lasting process, but are generally short-term programs. The HPSF clarifies theoretical concepts, their practical implementation via case studies and outlines intervention components and tools useful for sports federations in their implementation of HP.The guidelines developed in this study are intended to facilitate national sports federations to acknowledge/understand, reinforce/underpin and foster current and further investment in HP.